FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU K3 PADA PEKERJA DI AREA PENGGOLAHAN MINYAK KELAPA PT. INHIL SARIMAS KELAPA INHIL - LPPM Al-Insyirah (STIKes Al-Insyirah Pekanbaru, 2016)
Work accidents may occur by environmental and human factors, most of the accidents in the workplace caused by human action / behavior unsafe work. Data PT. Coconut Sarimas Inhil show cases of occupational accidents from year to year tends to decrease, but the case was never lost (zero accident). Intention of this research is what is there factors associated with worker occupational health and safety behavior in coconut oil manufacturing area of PT. Inhil Sarimas Kelapa year 2015. This research method is analytic quantitative of observasional with research desain use transversal crosscut approach (sectional cross) its responder is the worker in coconut oil manufacturing area of PT. Inhil Sarimas Kelapa. This research sampel counted 82 people in coconut oil manufacturing area. Technique intake of sample is total sampling. Analysis the used is analysis univariat and bivariat and with test of chi square. Use is data processing and kuesioner use computerization. Result of research show there are relation between knowledge (P value 0,023, nilai OR 3,125), perception(P value 0,043, nilai OR 2,769), attitude (P value 0,010, nilai OR 3,638), tenure (P value 0,010, OR 4,009), motivation (P value 0,009, OR 3,629). Thera are not relation between, education, monitoring, and sanction. Advised to relevant agencies, namely PT. Inhil Sarimas Coconut particularly Dept. Coconut Oil manufacturing, provide insight and training on safety behavior regularly to their workers, as well as provide various bonuses (reward) to workers who behave safety so other workers are motivated to behave K3 safe as well.